Testing for sources of electoral competition under authoritarianism: an analysis of Russia's gubernatorial elections. Issue 5 (3rd September 2017) - Gorokhovskaia, Yana
Abstract: What drives electoral competition in competitive authoritarian regimes? Most scholarship has assumed that the outcome of these elections is decided by regime manipulation alone. Using three rounds of newly reinstated gubernatorial elections in Russia's regions, I test this assumption. I identify three distinct measures of competition calibrated to authoritarian elections and assess whether voter preferences or regime manipulation best explain the degree of electoral competition. Relying on new data on protests across Russia's regions, I find that regions with high protest activity have more contested elections with narrower margins of victory. The results also confirm recent scholarship highlighting the importance of voter turnout for delivering pro-regime victories.